2020 29th IEEE International Conference on Robot and Human Interactive Communication (RO-MAN) 2020
DOI: 10.1109/ro-man47096.2020.9223456
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Robot’s Facial Expressions on Children’s First Impressions of Trustworthiness

Abstract: Facial expressions of emotions influence the perception of robots in first encounters. People can judge trustworthiness, likability, and aggressiveness in a few milliseconds by simply observing other individuals' faces. While first impressions have been extensively studied in adult-robot interaction, they have been addressed in child-robot interaction only rarely. This knowledge is crucial, as the first impression children build of robots might influence their willingness to interact with them over extended pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 37 publications
1
34
1
Order By: Relevance
“…Concerning perceived competence, we did not find any significant effect of regulatory focus on the dependent variables, QIma (U(N Prom 29, N Prev 27) 360, z −.58, p .561, r −. Other studies focused on assessing trust in social robots have suggested that children's perception of trust in a robot is rather inferred from initial impressions of competence and likability (Calvo-Barajas et al, 2020).…”
Section: Children's Perception Of Likability Competence and Trustworthinesscontrasting
confidence: 51%
“…Concerning perceived competence, we did not find any significant effect of regulatory focus on the dependent variables, QIma (U(N Prom 29, N Prev 27) 360, z −.58, p .561, r −. Other studies focused on assessing trust in social robots have suggested that children's perception of trust in a robot is rather inferred from initial impressions of competence and likability (Calvo-Barajas et al, 2020).…”
Section: Children's Perception Of Likability Competence and Trustworthinesscontrasting
confidence: 51%
“…The 'novelty effect' in HRI is gathering increasingly more attention [4,59], as researchers try to determine whether the effects found in short-term interactions generalise across repeated encounters. This is especially relevant in the domain of trust, where children may form immediate impressions of trustworthiness [16]. As such, long-term studies will be of crucial importance to understand the trajectory of trust development, breakdown, and recovery in cHRI.…”
Section: Qualitative Observationsmentioning
confidence: 99%
“…Accordingly, parallel to interpersonal trust, numerous studies have found a relevance of determinants related to robot competence for trust development in HRI. These include the robot's perceived competence based on its facial expressions (Calvo-Barajas et al, 2020), the robot's reputation in the sense of knowledge about its reliance (Bagheri and Jamieson, 2004), its previous performance (Chen et al, 2010, Lee andSee, 2004), as well as its actual performance (Chen et al, 2010). Similarly, Robinette et al (2017) found that poor robot performance was associated with a drop in self-reported trust of humans in robots, which was in turn correlated with their decision to use the robot for guidance (Robinette et al, 2017).…”
Section: Transferability Of Determinants Of Trust Development In Interpersonal Interaction To Hrimentioning
confidence: 99%